(untitled) (International Journal of Engineering and Computer Science, 2016)
In this paper Parikh Matrices over context-free languages are investigated. Context-free grammars for Natural languages are a developing area of investigation. Parikh matrix is a significant tool of Formal languages. Context-free language is a kind of formal language. Parikh matrix can be used in context-free language. A context-free grammar for Bengali language is also a developing area of investigation. As a case study in this paper Bengali letters, Bengali words and Bengali sentences are studied by using Parikh matrix.